TINJAUAN YURIDIS TERHADAP HARTA BERSAMA YANG DIJADIKAN SEBAGAI JAMINAN FIDUSIA (STUDI PADA PT. PEGADAIAN (PERSERO) CABANG MEDAN SUNGGAL) - RENI ANGGRAINI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Hasim Purba, SH, MHum2.  Dr. Utary Maharany Barus, SH, MHum3.  Dr. Yefrizawati, SH, MHum The result of the research shows that according to Article 36, paragraph 1 of Law No. 1/1974 on Marriage states that the marriage couple can use joint property with the consent of both of them. Therefore, the credit contract with joint property used as fiduciary collateral has to be the consent of both husband and wife. In the case of the credit contract with join property used as fiduciary collateral at PT. Pegadaian (Persero), Medan Sunggal Branch, the personnel of the pawn shop should identify the concept of 5C toward clients, whether it has been obtained during the marriage. Both husband and wife have to know, to agree, to sign the whole credit contract before a Notary at the pawn shop so that both of them will receive the loan together and will pay off the loan together, too. When there is non-performing loan, the pawn shop management will call up the clients and send the demand for payment. If it fails, the process of auction of fiduciary collateral is performed, witnessed by the police.Keywords: Joint Property, Credit, Fiduciary